"Affairs" and the Actual World. Issue 3 (3rd July 2021) - Guorong, Yang
Abstract: The actual world, which surpasses the original state of being, consists in "affairs" ( shi ). Affairs can be understood as human activity and its outcomes. From the perspective of an abstract metaphysics, "things" ( wu ) appear to be independent of affairs and to possess ontological priority. However, through properly understanding the actual world we see that in fact affairs manifest the more fundamental import. Humans interact with things through affairs, and in this sense, the relations of humans with things are mediated by the relations of humans with affairs. Things manifest their diverse meaning only through incorporation into affairs. Additionally, the actual world formed through human activity gives rise to both the realm of fact and the realm of value, and affairs thus provide fundamental grounds that unify fact and value. In understanding the actual world, we must avoid reducing affairs, first, to merely matters of the mind and second, to merely matters of language. Affirming that it is based in affairs means that the actual world surpasses the original state of being while also committing us to its reality.